Biological functions of the Olig gene family in brain cancer and therapeutic targeting - Szu, Jenny I.; Tsigelny, Igor F.; Wojcinski, Alexander; Kesari, Santosh (Frontiers in Neuroscience, 2023)
The Olig genes encode members of the basic helix-loop-helix (bHLH) family of transcription factors. Olig1, Olig2, and O regulate cellular specification and differentiation. Over the past decade extensive studies have established functional roles of Olig1 and Olig2 in development as well as in cancer. Olig2 overexpression drives glioma proliferation and resistance to radiation and chemotherapy. In this review, we summarize the biological functions of the Olig family in brain cancer and how targeting Olig family genes may have therapeutic benefit.